A Contrastive Rhetoric Study of Persuasion in TED Talks Narratives - Attiya, Ghada Elsayed Belal (Majallat al-baḥth al-ʻilmī fī al-ādāb, 2022)
Since 1984 thousands of stories have been told on stage in the platform known as TEDEX or TED TALKS. These were inspiring stories covering diverse areas of life and meant to persuade the audience of better well- being. The present paper investigates the powerful persuasive features present in twenty randomly selected Ted Talks narratives: ten American English and ten Egyptian Arabic narratives. The paper employs Cockcroft and Cockcroft's model of persuasion (2013) with its three tripartite divisions of Aristotle's Ethos, Pathos and Logos. The contrastive analysis is done within Marc Alexander's (2009) adapted version of Mann and Thompson's Rhetorical Structure Theory (1988), which best suits the data under investigation. The paper adds more items under the presentational and subject matter relations introduced by Mann and Thompson's RST, so that more types of utterances are easily identified and categorized. It also compares and contrasts the techniques used in both languages to examine the types employed for persuasion of the two different types of audience.